Combination therapy with dutasteride and tamsulosin for the treatment of symptomatic enlarged prostate - J Miller (Dove Medical Press, 2009)
J Miller, TH TarterSouthern Illinois University School of Medicine, Department of Surgery, Springfield, IL, USAAbstract: Benign prostatic hyperplasia (BPH) is a frequent cause of lower urinary symptoms, with a prevalence of 50% by the sixth decade of life. Hyperplasia of stromal and epithelial prostatic elements that surround the urethra cause lower urinary tract symptoms (LUTS), urinary tract infection and acute urinary retention. Medical treatments of symptomatic BPH include; 1) the 5α-reductase inhibitors, 2) the α1-adrenergic antagonists, and 3) the combination of a 5α-reductase inhibitor and a α1-adrenergic antagonist. Selective α1-adrenergic antagonists relax the smooth muscle of the prostate and bladder neck without affecting the detrussor muscle of the bladder wall, thus decreasing the resistance to urine flow without compromising bladder contractility. Clinical trials have shown that α1-adrenergic antagonists decrease LUTS and increase urinary flow rates in men with symptomatic BPH, but do not reduce the long-term risk of urinary retention or need for surgical intervention. Inhibitors of 5α-reductase decrease production of dihydrotestosterone within the prostate resulting in decreased prostate volumes, increased peak urinary flow rates, improvement of symptoms, and decreased risk of acute urinary retention and need for surgical intervention. Interim results of the ongoing Combination of Avodart and Tamsulosin (CombAt) study have shown combination therapy with the 5α-reductase inhibitor dutasteride and the α1-adrenergic antagonist tamsulosin offer significant improvements from baseline compared with either drug alone.Keywords: prostatic hyperplasia, 5α-reductase, dutasteride, tamsulosin